Die hard: necroptosis and its impact on age-dependent neuroinflammatory diseases - Smith, Kaitlan; Colie, Meagan; Moore, Trinity; Schisler, Jonathan C. (Frontiers in Cell Death, 2024)
The pro-inflammatory form of cellular death, necroptosis, is critical to age-related pathologies.Necroptosis primarily functions as an antipathogenic and antitumor biological mechanism by triggering inflammatory pathways within rogue cell bodies, resulting in cell death. Several neurodegenerative conditions have hallmarks of necroptosis, suggesting a potential role for this cell death pathway in the pathogenesis of neuroinflammation and neuronal cell death, likely through the release of pro-inflammatory cytokines that perpetuate inflammatory signaling and neurodegeneration. The receptor-interacting protein kinases 1 and 3 (RIPK1/3) signaling cascade is critical to necroptosis regulation; however, the complete mechanism behind necroptotic activation, regulation, and resolution remains incomplete. In cases where necroptosis is disadvantageous, such as neurodegenerative diseases, we lack effective pharmacological suppressors of necroptosis that could mitigate disease progression. Targeting regulatory proteins within the necroptotic signaling pathway has shown promise; however, the need for specific inhibitors limits therapeutic opportunities. This review focuses on necroptosis and its role in neuroinflammation and neurodegeneration in age-dependent disorders. We comprehensively detail the known necroptotic signaling pathways and potential signaling partners and discuss the ongoing therapeutic efforts in targeting and preventing active necroptotic signaling and their relevance to neuroprotection.